Rapid latex agglutination test for detection of staphylococcal enterotoxins A to E that uses high-density latex particles. - Fujikawa, H (1988)
A rapid reversed passive latex agglutination method that uses high-density latex particles for the detection of staphylococcal enterotoxins (SE) A to E was developed. It took 3 h for incubation, much less than the 16 h needed with a customary latex agglutination test for SE detection such as a commercial test kit (SET-RPLA; Denka Seiken Co. Ltd., Tokyo, Japan). The rapid test was shown to be highly specific and sensitive for SE detection (detection limit, about 0.5 ng of SE per ml), comparable to the SET-RPLA test. The rapid test was also efficient in SE detection in foods and culture supernatants of staphylococcal strains, similar to the SET-RPLA test. This showed that a rapid test with high-density latex particles is fully reliable for use.